A Comparison of the Species Composition of Arrenurus Duges (Arrenuridae: Hydrachnidia: Acari) in Turkey and Some Countries in Palearctic Region - Erman, Orhan; Arslan, Başak; Gülle, Pınar (Burdur Mehmet Akif Ersoy Üniversitesi, 2020)
This study aimed to determine the distributions, habitats and endemism rates of Arrenurus from Turkey. Similarity indices were determined between Turkey and some countries in the Palearctic Region. Sorensen and Jaccard similarity indices were used for the similarity comparisons. Both calculations show that Arrenurus fauna of Turkey has a high similarity with that of France, the Netherlands and Belgium, but the lowest similarity with Japan. It has also been reviewed the contributions made to the genus Arrenurus in Turkey. Additionaly, the female of Arrenurus dileri Boyacı and Özkan 2004 was misidentificated, it is determined Arrrenurus walkanoffi (Viets, 1926).

Bu çalışmada, Türkiye’den kaydedilmiş Arrenurus türlerinin dağılım, habitat ve endemizm oranlarının verilmesi amaçlanmıştır. Türkiye ve bazı Palearktik Bölge ülkelerinin arasındaki benzerlik hesapları yapılmıştır. Bu amaçla, Sorensen ve Jaccard benzerlik endeksleri kullanılmıştır. Her iki hesaplama sonucunda Türkiye Arrenurus faunası Fransa, Hollanda ve Belçika ile yüksek oranda benzerlik gösterirken, en düşük benzerlik Japonya ile gözlenmiştir. Ayrıca Türkiye Arrenurus cinsine yapılan katkılar da gözden geçirilmiştir. Arrenurus dileri Boyacı ve Özkan 2004’nin dişisi yanlış teşhis edilmiş olup, teşhis edilen örneklerin Arrrenurus walkanoffi (Viets, 1926)’ye ait olduğu belirlenmiştir.
Türkiye ve Bazı Palearktik Bölge Ülkelerinin Arrenurus Duges (Arrenuridae: Hydrachnidia: Acari) Türlerinin Karşılaştırılması